Edukasi Tindakan Pencegahan Cyber-Bullying Dan Pengenalan Istilah Bahasa Inggris Yang Sering Digunakan Oleh Pelaku - Nurhasanah Halim; Susilawati; Retno Dwigustini (CV. Multi Kreasi Media, 2023)
Cyberbullying is a type of internet bullying that has become increasingly frequent among children and teenagers as technology has advanced. As a result, parents must be knowledgeable about cyberbullying in order to support their children and adolescents in interacting with the virtual world, especially if one day they experience cyberbullying. One effort that can be made is to provide education about cyberbullying and get to know the various terms related to it. This educational activity regarding cyberbullying is carried out through community service activities by lecturers from Bina Sarana Informatika University, to members of the Communication Forum of the Taklim Council at Jami' Al Muttaqin Mosque, Central Jakarta. The method used is Community-Based Participatory Research Design. This community service activity yielded great outcomes since the participants were able to identify the terminology used in cyberbullying. The participants also showed enthusiasm during the activity. As an implication of this research, it is expected that similar educational activities will be frequently organised by related parties in the community as a form of digital literacy for smarter and wiser use of technology.